Radionuclide concentrations in raw and purified phosphoric acids from Brazil and their processing wastes: implications for radiation exposures - Conceição, Fabiano Tomazini da [UNESP]; Pereira Antunes, Maria Lucia [UNESP]; Durrant, Steven F. [UNESP] (Springer, 2012)
Radionuclides from the U and Th natural series are present in alkaline rocks, which are used as feedstock in Brazil for the production of raw phosphoric acid, which can be considered as a NORM (naturally occurring radioactive material). As a result of the purification of raw phosphoric acid to food-grade phosphoric acid, two by-products are generated, i.e., solid and liquid wastes. Taking this into account, the main aim of this study was to evaluate the fluxes of natural radionuclide in the production of food-grade phosphoric acids in Brazil, to determine the radiological impact caused by ingestion of food-grade phosphoric acid, and to evaluate the solid waste environmental hazards caused by its application in crop soils. Radiological characterization of raw phosphoric acid, food-grade phosphoric acid, solid waste, and liquid waste was performed by alpha and gamma spectrometry. The (238)U, (234)U, (226)Ra, and (232)Th activity concentrations varied depending on the source of raw phosphoric acid. Decreasing radionuclides activity concentrations in raw phosphoric acids used by the producer of the purified phosphoric acid were observed as follows: Tapira (raw phosphoric acid D) > Catalo (raw phosphoric acids B and C) > Cajati (raw phosphoric acid A). The industrial purification process produces a reduction in radionuclide activity concentrations in food-grade phosphoric acid in relation to raw phosphoric acid produced in plant D and single raw phosphoric acid used in recent years. The most common use of food-grade phosphoric acid is in cola soft drinks, with an average consumption in Brazil of 72 l per person per year. Each liter of cola soft drink contains 0.5 ml of food-grade phosphoric acid, which gives an annual average intake of 36 ml of food-grade phosphoric acid per person. Under these conditions, radionuclide intake through consumption of food-grade phosphoric acid per year per person via cola soft drinks is not hazardous to human health in Brazil. Considering these annual additions of (238)U, (226)Ra, (232)Th and (40)K, and since these radionuclide should be homogeneously distributed in the upper 10 cm of soils with an assumed apparent density of 1.5 g/cm(3), a maximum increase of 0.19 +/- A 0.03 Bq kg(-1) of soil is expected for (238)U and (234)U. Thus, the addition of solid waste as phosphate fertilizers to Brazilian agricultural soils does not represent a hazard to the ecosystem or to human health.
Keywords: NORM; Raw phosphoric acids and by-products; Environmental hazards